Questing Ticks Drink Water - Haman, Colter; Beals, Brendan; Park, Yoonseong (My University, 2017)
Survival of questing ticks in the filed depends on uptaking water from environment. With there being little known about the amount of water that ticks consume, we were interested in whether drinking water is a common phenomenon in different species of ticks: Amblyoma americanum, Rhipicephalus sanguineus, Dermacentor variabilis, and Ixodes scapularis. The question was expanded to whether the ticks drink blood through capillary tubes and which internal organ is responsible for the absorption of the liquid uptake. In capillary feeding of water for an hour, all four species drank water: 0.17uL in R. sanguineus, 0.35 uL in A. americanum, 0.39 uL in D. variabilis. D. variabilis and I. scapularis drank blood, whereas R. sanguineus and A.americanum did not drink blood in the capillary feeding system. In observations of internal organs using rhodamine 123 as a fluorescent tracer, we found that A. americanum and I. scapularis drank liquid through type 1 acini of the salivary glands and their midgut, while R. sanguineus and D. variabilis drank through type 2/3 acini. We found that different species ticks show significantly different ways of obtaining water from environment.